Evaluating the level of readiness to teach science in the light of the information, media, and technology skills among undergraduate students at the Faculty of Education, King Khalid University (Journal Of Educational and Psychological Researches, 2022)
This research aimed to evaluate the level of readiness to teach science in the light of the information, media, and technology skills among undergraduate students at the Faculty of Edu-cation, King Khalid University. To achieve this goal, a descriptive and analytical approach was used. A list of readiness to teach science was prepared in the light of Information, media, and technology skills, and in the light of this list, a cognitive test, observation sheet, and attitude scale were prepared to assess readiness to teach science in its three aspects, cognitive, behavioral, and emotional. The sample of the research consisted of (42) students enrolled in field training courses at the sixth, seventh and eighth levels. Research tools were applied during the second semester of the academic year 1440/1441 AH. The results of the research revealed that the cognitive aspect, the behavioral aspect, the emotional aspect of the readiness to teach, and the total readiness to teach science in the light of Information, media, and technology skills are statistically significantly, which are less than the required level determined by (80%) of the overall performance. As the percentages of these levels, respectively reached (61.3%), (61.1%), (63%), (62.4%) of the overall performance. The results also revealed that there are no statistically significant differences at the level (0.05) between the degree of readiness to teach science in light of Information, media, and technology skills of the research sample according to the academic level. The research ended with a set of recommendations and proposals closely related to the results of the research.